2017
DOI: 10.3389/fneur.2017.00430
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Therapeutic Inertia in Multiple Sclerosis Care: A Pilot Randomized Trial Applying the Traffic Light System in Medical Education

Abstract: BackgroundPhysicians often do not initiate or intensify treatments when clearly warranted, a phenomenon known as therapeutic inertia (TI). Limited information is available on educational interventions to ameliorate knowledge-to-action gaps in TI.ObjectivesTo evaluate the feasibility and efficacy of an educational intervention compared to usual care among practicing neurologists caring for patients with multiple sclerosis (MS).MethodsWe conducted a pilot double-blind, parallel-group, randomized clinical trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Of interest is the comparison of TI in neurologists from Canada vs. that of neurologists from other countries (Argentina, Chile, and Spain) ( 22 ). Our analysis revealed that Canadian participants had a significantly lower TI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest is the comparison of TI in neurologists from Canada vs. that of neurologists from other countries (Argentina, Chile, and Spain) ( 22 ). Our analysis revealed that Canadian participants had a significantly lower TI.…”
Section: Discussionmentioning
confidence: 99%
“…Values lower than 10 healthy-years of survival would represent aversion to the risks of treatment, whereas higher values would represent risk-prone individuals. A study with a similar protocol and design was conducted in Argentina and Chile in 2017 ( 22 ). Details of the protocol were published in previous publications ( 17 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the TLS was feasible and promising by showing a trend towards a reduction in TI compared to controls (OR 0.57; 95% CI 0.26-1.22). 8 In another study, the authors assessed herding among 96 neurologists with expertise in MS. Herding is a phenomenon that can occur in MS when neurologists follow a therapeutic recommendation by a colleague even though it is not supported by best practice clinical guidelines. Nearly 8 out of 10 neurologists exhibited herding.…”
Section: Application To Medical Decision-makingmentioning
confidence: 99%
“…For example, classic studies in consumer research showed that the higher the number of available options may negatively influence consumer’s decisions due to information overload ( 10 ). Moreover, the time of the day influences assertive decisions, phenomenon called “decision fatigue.” Similarly, 7 out of 10 neurologists expressed TI as a result of these factors and lower tolerance to uncertainty ( 11 ). This is not surprising given that neurology practice is a medical specialty with higher incidence of physicians’ biases and burnout, and MS being a neurological condition leading the paradigm of multiple therapeutic choices with ongoing developments—altogether the perfect combination for TI ( , accessed December 15, 2017).…”
mentioning
confidence: 99%